2018
DOI: 10.7554/elife.40070
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4-dependent glymphatic solute transport in the rodent brain

Abstract: The glymphatic system is a brain-wide clearance pathway; its impairment contributes to the accumulation of amyloid-β. Influx of cerebrospinal fluid (CSF) depends upon the expression and perivascular localization of the astroglial water channel aquaporin-4 (AQP4). Prompted by a recent failure to find an effect of Aqp4 knock-out (KO) on CSF and interstitial fluid (ISF) tracer transport, five groups re-examined the importance of AQP4 in glymphatic transport. We concur that CSF influx is higher in wild-type mice t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
437
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 470 publications
(507 citation statements)
references
References 73 publications
22
437
1
Order By: Relevance
“…Our simulations point to two main reasons why arterial pulsations cannot drive unidirectional fluid flow in the PVS. First, direct measurement of cortical arteriole diameters in mice using two-photon imaging shows that the amplitude of the heartbeat-driven pulsations is small (1-4% peak to peak change in arterial diameter 6,50,51 ). In humans, CT angiography has shown that pulsations drive only a maximum of 4-6% 52,53 change in the volume of the MCA (2-3% change in diameter assuming a cylindrical geometry).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our simulations point to two main reasons why arterial pulsations cannot drive unidirectional fluid flow in the PVS. First, direct measurement of cortical arteriole diameters in mice using two-photon imaging shows that the amplitude of the heartbeat-driven pulsations is small (1-4% peak to peak change in arterial diameter 6,50,51 ). In humans, CT angiography has shown that pulsations drive only a maximum of 4-6% 52,53 change in the volume of the MCA (2-3% change in diameter assuming a cylindrical geometry).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experimental evidence available, we speculate that two possible mechanisms that could drive CSF flow in the PVS, namely, CSF production in the choroid plexus and osmotic pressure differences across astrocytic end feet. CSF flow through the PVS and into the brain is severely affected in aquaporin-4 (AQP4) knockout mice 1,50 . The AQP4 channel is selectively permeable to water 61,62 and is present in the choroid plexus 63 and the astrocytic endfeet 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of Aqp4 in glymphatic function is, however, still a matter of discussion. The development of a functional glymphatic system in mice was shown to be correlated with the expression of Aqp4 at the astrocyte endfoot-vascular interface [62], and using several lines of Aqp4deficient mice, glymphatic tracer transport was shown to depend on intact Aqp4 function [63]. It has, however, also been argued that Aqp4 may not be solely responsible for fluid transport, but that diffusion is in fact an important regulator of paravascular flow.…”
Section: Paravascular Flowmentioning
confidence: 99%
“…Impairment of meningeal lymphatics induced amyloid accumulation, and AAV1-CMV-mVEGF-C treatment enhanced CSF drainage and meningeal lymphatics function and improved spatial learning and memory. 2 As water channel aquaporin-4 (AQP4) in astrocytic end feet plays a role in glymphatic flow and maintained CSF influx in Aqp4 knockout mice 15 . In AD, AQP4 were expressed abnormally and mislocalized.…”
Section: Discussionmentioning
confidence: 99%